Proportion of Sputum Smear Non-Converters Among Adult Patients With Bacteriologically Confirmed Pulmonary Tuberculosis in Chattogram District of Bangladesh (Journal of Chittagong Medical College Teachers' Association, 2025)
Background: Non converters are becoming a big issue now a days. Many of the non-converters become drug resistant later on. There are many factors causing a TB patient to becomes non converter after the intensive phase of treatment. The objectives of the current study were to measure the proportion of non-converters among the adult bacteriologically confirmed pulmonary tuberculosis patient in Chattogram district and also to find out the factors associated with the development of non conversion.Materials and methods: This was a descriptive cross sectional study. A total 211 patients were enrolled in this study purposively from different upazilas of Chattogram. Data was collected from hospital records and from direct interviewing the patients. Then compiled, calculated, summarized and analyzed using different computer-based software and presented in different tables and diagrams.Results: Among the total 211 respondents 11 were found non-converters, e.g. 5.21%. Mean age of all converters was 46.78±14.52 years whereas mean age of nonconverters was 55.36±9.91 years. The mean age difference was significant. Among non-converters 08(72.73%) were male and 03 were female (27.27%) the sex difference was found non-significant in this study. Among all the patients 51(24.17%) were smoker while out of 11 non converters 7(63.63%) were found smokers, making smoking significantly associated with non-conversion. Among the respondents 45 (21.33%) had co-morbidity. Only COPD and DM were found associated with non-conversion where no HTN or CKD patients were found non converters. Test showed that there was significant relationship between sputum smear grading ³2+ and nonconversion with odds ratio 19.11.Conclusion: This study found the proportion of adult nonconverters among the bacteriologically confirmed pulmonary tuberculosis patients after two months of intensive phase of anti TB treatment is like most of other south Asian countries. Factors found significantly associated for being non converters are increased age, smoking habit as well as comorbidities like chronic obstructive pulmonary disease and diabetes mellitus. Pretreatment sputum smear grading also had significant impact on causing non conversion.JCMCTA 2024 ; 35 (1) : 142-146